PERAN KOMITMEN TUJUAN MEMEDIASI HUBUNGAN BUDGET PARTICIPATION TERHADAP KINERJA MANAJERIAL - I Gst Ayu Wirati Adriati; Ida Ayu Oka Martini (JUIMA : JURNAL ILMU MANAJEMEN, 2020)
The budgeting process involves various parties in the company and the budget cannot be analyzed only through the accounting field, but must also consider the behavior considerations involved. The purpose of this study is 1) to determine the effect of budget participation on managerial performance, 2) to determine the effect of budget participation on goal commitment and 3) to determine the effect of goal commitment effect on managerial performance. Data collection techniques using a questionnaire with 32 managers and assistant managers as respondents. The data collected was analyzed by path analysis with the AMOS program. The results showed that 1) Budget Participation had a direct and positive and significant effect on Managerial Performance. 2) Budget Participation has positive and significant direct effect on the Commitment of Goals. 3) Commitment on the Goal has a positive and significant direct effect on Managerial Performance. 4) Commitment The objective is to act as a partial mediator in the relationship of Budget Participation variables to Managerial Performance.